Fiscal and Regional Investment Synergy to Promote Industrial Downstreaming in North Kalimantan Province - Aslan A; Khotibul Umam Isnanto; Elvi Olga Vania (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Kalimantan Utara Province possesses substantial potential in the natural resources sector; however, the contribution of the manufacturing industry to Gross Regional Domestic Product (GRDP) remains low due to the dominance of raw material exports. This study aims to examine the condition and role of regional fiscal policy in Kalimantan Utara Province in supporting the industrial downstreaming process; to analyze the direction, characteristics, and effectiveness of investment (both public and private) entering the province in accelerating industrial downstreaming; and to identify the optimal form of synergy between regional fiscal policy and investment to promote sustainable industrial downstreaming in the region. The research employs panel data analysis using the Fixed Effect Model (FEM) with natural logarithm (ln) transformation, based on data from 2015â€“2024 covering five regencies/cities in Kalimantan Utara Province. The independent variables include Regional Own-Source Revenue (PAD), Capital Expenditure (BM), Fiscal Independence Ratio (RK), Domestic Direct Investment (PMDN), Foreign Direct Investment (PMA), and Industrial Population (JPI), with Industrial Downstreaming as the dependent variable. The results indicate that the Fixed Effect Model is the most appropriate model, suggesting differences in fiscal characteristics across regions. The PMA variable has a positive and significant effect on industrial downstreaming (p = 0.017), while PAD has a positive but not statistically significant effect (p = 0.067). Other variables, including BM, RK, PMDN, and JPI, do not have significant effects. The Adjusted RÂ² value of 0.628 indicates that approximately 62.8% of the variation in industrial downstreaming can be explained by regional fiscal and investment variables.